Sistem Paylater dalam Transaksi Digital dan Implikasinya terhadap Hukum Fikih Muamalah Kontemporer - Haerunnisa Haerunnisa; Arif Sugitanata (Program Studi Hukum Ekonomi Syariah, 2025)
This study aims to analyze the impact of the paylater system on the dynamics of digital transactions in Indonesia and to examine its legal status from the perspective of contemporary Islamic commercial jurisprudence (fiqh al-mu’āmalāt). Employing a qualitative research design grounded in library research, this study draws upon academic literature, official financial institution reports, and relevant Islamic legal sources. The findings reveal that the paylater system has transformed consumer behavior in Indonesia—from prudence-based spending to a consumption pattern driven by instant credit access. While it contributes to financial inclusion, particularly for populations underserved by formal financial institutions, the system also poses significant risks of consumer debt, especially among youth with low financial literacy. From the perspective of fiqh al-mu’āmalāt, paylater schemes are categorized under deferred payment sales contracts (al-bay’u bi thaman ājil), which are permissible provided that contractual conditions are met. However, in digital practice, these schemes often involve elements of gharar (uncertainty) due to the lack of clear information and the potential for riba (usury) stemming from unauthorized interest and penalty mechanisms. Furthermore, the hybrid nature of these contracts—combining elements of loans, sales, and services—introduces additional legal complexities. Therefore, the paylater system must be restructured in accordance with the principles of justice, transparency, and consumer protection, aligning with the objectives of Islamic law (maqāṣid al-sharī’ah). These findings underscore the urgency of implementing sharia-compliant oversight in digital financial services and enhancing consumer literacy as a necessary adaptation of Islamic jurisprudence to the evolving digital economy.